Scientific Learning and Inquiry-Based Learning Management in Learning Transformation at School - Najma Khairunnisa; Irawan; Rohmat Mulyana Sapdi; Syifa Delfiani Gunawan (Al-Qalam Institue, 2026)
This study aims to analyze the implementation of Scientific-Based Learning (SBL) and Inquiry-Based Learning (IBL) in transforming instructional practices in Islamic education through an educational management perspective, including planning, implementation, evaluation, and teacher professional development. Employing an explanatory mixed-method design, data were collected through semi-structured interviews with teachers and school leaders, classroom observations, document analysis, and questionnaires administered to the majority of teachers at Sekolah Tunas Unggul. The findings indicate that the integration of SBL and IBL has shifted instructional practices from a rational–practical orientation toward a scientific, student-centered approach emphasizing inquiry, reflection, and knowledge construction. From a management perspective, instructional transformation is reflected in systematic curriculum planning, clearer and measurable learning objectives, improved instructional organization, and the integration of Islamic values within contextual inquiry and project-based learning. Initial outcomes include increased student engagement, enhanced project quality, and improved critical thinking skills. However, the implementation remains constrained by limited teacher methodological literacy, insufficient facilities, time management challenges, and inconsistent data-based assessment practices. The study implies that sustainable scientific-based instructional transformation in Islamic education requires strong institutional leadership, continuous professional development, adequate resource management, and aligned educational policies.